A prática de leitura e escrita de alunos do ensino médio sobre física moderna e contemporânea - Ana Lucia Lopes Correa (2003)
In this research we analyze the practice of reading and writing by students in secondary school physics classes. To do this, teaching sequences were developed with the topic o Modern and Contemporary Physics (MCP). The teaching sequences were used with students in a secondary school class of a federal public school, chosen for being an exemplary representative for the object of our study. Our objective was to discover the indicators of progressive appropriation of scientific language, through activities using scientific explanatory texts (SETs), didactic texts, didactic and full-length science fiction films, transparencies and problem-solving. We also question the influence of SETs and the presence of different types of language in the written responses of the students as the teaching sequences progressed. This research considers learning to be an essentially socio-cultural process mediated by language (Vygotsky, 1999) and our concepts of the genres of discourse, topics and Bakhtins (2002) intertextuality. This reference is operationalized based on categories constructed by us and adapted from Braga (2003) and Zamboni (1997). The research data, results of analysis of students written responses, were organized to allow the recognition of changes and permanent features expressed in student writing. We conclude that the intertextuality shown in the written responses of the students indicates an appropriation of the indicators of different genres established by the teaching sequences. The description of physical entities migrates toward the description of physica phenomena, showing what we suppose to be an evolution in the character of the students written responses. We observe that the interlocutor of the students continues to be restricted to the classroom, in that the writing is specifically didactic discourse. Our results indicate that the SETs can be used as a strategy to teach the content o physics. Thus, the classroom provides opportunities for the discussion of means and methods of scientific production, a situation that contributes to students drawing closer to doing science.